More Than Cholesterol Catabolism: Regulatory Vulnerabilities in Mycobacterium tuberculosis - Bonds, Amber C. (Curr Opin Chem Biol, 2018)
Mycobacterium tuberculosis (Mtb) is the epitome of persistent. Mtb is the pathogen that causes tuberculosis, the leading cause of death by infection worldwide. The success of this pathogen is due in part to its clever ability to adapt to its host environment and its effective manipulation of the host immune system. A major contributing factor to the survival and virulence of Mtb is its acquisition and metabolism of host derived lipids including cholesterol. Accumulating evidence suggests that the catabolism of cholesterol during infection is highly regulated by cholesterol catabolites. We review what is known about how regulation interconnects with cholesterol catabolism. This framework provides support for an indirect approach to drug development that targets Mtb cholesterol metabolism through dysregulation of nutrient utilization pathways.